(untitled) (Journal of Comparative & International Higher Education, 2024)
Contemporary HEIs are characterized by internationalized classrooms and diverse learning spaces that blend various linguistic and cultural backgrounds. Achieving the benefits of diversity falls short however, and challenges remain unaddressed since academics, central to unlocking the full potential of the international classroom, lack competence, resources, and tools. Despite universities offering CPD, these suffer from low enrollment and a high drop-out rate. A literature review confirms that the voice of academics has been neglected in designing CPD. We investigated the perceptions and needs of academics in the context of a medium-sized university in Sweden using a survey. The findings indicate that the design and delivery of CPD would benefit from adopting an andragogical approach. There is a valuable lesson for designers and deliverers of CPD in academia: listen to the needs of your audience, involve them in design and delivery, acknowledge their experience, and build collaborative learning opportunities.